O uso do streaming musical sob o enfoque da lei de direitos autorais brasileiro : uma análise do spotify à luz da teoria dos direitos humanos e fundamentais - Silva, Cristina Baum da (2023)
Through streaming, royalty payment algorithms, and playlist recommendation algorithms, Spotify has been violating norms of fundamental cultural rights, fundamental copyright and the human dignity of music composers. The present work was carried out through the hypothetical-deductive method and is introduced by presenting how streaming, a technology of instant data transmission, transformed the music industry that was on the verge of bankruptcy with the uncontrollable uploads and downloads via Napster, μTorrent and The Pirate Bay. Given the relevance of the use of technologies on fundamental rights and following the area of concentration “Constitutional Foundations of Public Law and Private Law” of this Graduate Program in Law, the first chapter discusses cultural rights from the international, constitutional, and other legal norms of protection of culture, as well as UNESCO's concern with the algorithmic discrimination that occurs in the music industry. In the second chapter, a historical and bibliographic review of copyright, of the phonographic industry is made, as well as it is treated on the role of ECAD in the collective management of copyright in Brazil. This chapter concludes by pointing out the effectiveness of fundamental rights in the private relations between composers and record labels. In the third chapter, the history of Spotify is narrated, explaining how the company has been behaving with the demands of musical composers in relation to the value of streamshare, the apportionment of copyright and how the platform has been acting to assist in the growth of artists. It is concluded that Spotify is a technology company that aims at its growth in the stock market and has been instrumentalizing musical composers.